Reflections on Academic Analysis model in community higher education institutions: pilot study - Paz, Fabio Josende; Cazella, Silvio Cesar (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
Academic Analytics is a relatively new area that brings analytics and business intelligence concepts to higher education. This article aims to report the results of a pilot study of the application an Academic Analytics model in a Community Institution of Higher Education. The research method was experimental and used content analysis as a methodology. The results are partial, but they are promising, we highlight the optimization of time, the quality of the information presented and the good evaluation of the coordinators in relation to support decision-making, helping the management process.